Developing Students Vocabulary at Elementary School by Using Words Game - Abdul Syakir; Elihami Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The objective of this research was to know whether by using words games can improve students' vocabulary skills. Researchers used a pre-experimental research design. The sample of this study was selected using totally sampling. The research instrument used pre-test and post-test. This research was conducted in the elementary School. Data from the results of this study indicate that there is a significant increase in the amount of treatment given. In the experimental class, students' vocabulary skills improve. In the experimental class there was a treatment given, using a Words game. The improvement can be proven by the mean post-test score of 80.00 and it can be concluded that the use of words games can improve students' vocabulary skills.